Valores referenciales de hemoglobina en la población estudiantil femenina de 12 a 19 años de los Colegios Fiscales de la ciudad de Loja - Ríos Moreira, Janina Margarita (2010)
Standardization of Hematology Reference Values contributes to accurate diagnosis of diseases such as anemia, taking into account that in each population variability values can be made because of factors such as lifestyle, height, age, gender, race and geographical location ; what they do need their own reference values of the medium, allowing the physician to give an accurate diagnosis of hematologic diseases. This research is showing with Reference Values of hemoglobin in Female students in our city, exams were realized in adolescents between age 12 and 19, belong to Matutine Section in Fiscal High Schools of Loja city, situated to 2060 meters above the sea level. The investigated group was realized in a random form involving to students age 12 and 19, the tests were applied to 472 female students previous informative conferences to get permission and coin realize their clinic exams. Process to determine hemoglobin was realized through automatic method, statistic analysis was realized about the normal parameters in the complementary test such as: total proteins, iron, uro-analysis, copro-analysis and blood occult. The analysis of the results was made in the statistical program EPI-INFO 6, which allowed us to establish a data bank, the same used to feed the existing database to coordinate our career. Statistic results are indicated by bars and percentages. Average of hemoglobin was 14.1 g/dl, with a standar deviation of 0.81 g/dl; and the Referential Values gotten was between 12.5 and 16 g/dl; which will be a great support to medic diagnostic. The dissemination of results was performed in the auditorium of the Department of Human Health at the National University of Loja, in the presence of Presidents of Colleges, university authorities and the community, especially in our area. CLAVE WORDS: Hemoglobin, referential values, adolescents women between age 12 and 19.